Androgen ablation for low-risk prostate cancer is common among male hip fracture patients. (April 2014) - Kaipia, Antti; Riikonen, Jarno; Norja, Heikki; Huhtala, Heini; Laitinen, Minna
Abstract Objective. This study aimed to evaluate the prevalence of androgen deprivation therapy (ADT) among male hip fracture patients with prostate cancer and to analyse their indications for ADT with regard to prostate cancer risk classification. Material and methods. Tampere University Hospital records were screened for International Classification of Diseases, 10th revision (ICD-10) diagnoses S72.0–72.2 in 1998–2008 to identify hip fractures among males. Prostate cancer and fracture characteristics and concomitant medications were recorded. Fracture patients with prior prostate cancer diagnosis were compared to control patients from the Tampere University prostate cancer database and the risk factors for fracture were analysed by binary logistic regression analysis. Results. In total, 133 patients (11.0% of hip fractures) had a prostate cancer diagnosis prior to fracture; of these, 111 (84.1%) had osteoporotic, 14 (10.6%) pathological and seven (5.3%) high-energy fractures. Furthermore, 117 (88.0%) of fracture patients had received ADT for their prostate cancer. The mean interval between castration and fracture was 5.9 years (median 4.6 years). Of the fracture patients with prostate cancer, 24.8% had been primarily castrated for a low-risk disease. In multivariate analysis, ADT was a significant risk factor for fracture among low [odds ratio (OR) 3.02, 95% confidence interval (CI) 1.14–8.01, p = 0.027], intermediate (OR 4.52, 95% CI 1.32–15.40, p = 0.016) and high-risk prostate cancer patients (OR 5.85, 95% CI 1.30–26.30, p = 0.021). Conclusions. Hormonally treated prostate cancer is a major risk factor for osteoporotic hip fracture in males. Nearly a quarter of the prostate cancer patients suffering a hip fracture had been treated by primary castration despite having low-risk prostate cancer, emphasizing the importance of patient selection and timing for ADT.